Molecular investigation of the chlorine and antibiotic resistance mechanisms of Escherichia coli isolated from natural water sources in the Western Cape - Krige, Marilyn (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Pathology. Medical Microbiology))--University of Stellenbosch, 2009.